Adverse postoperative outcomes associated with perioperative blood transfusion in gynecologic oncology surgery. Issue 4 (15th February 2023) - Swift, Brenna E; Maeda, Azusa; Bouchard-Fortier, Geneviève
Abstract : Objective: To examine the incidence of perioperative blood transfusion and association with 30 day postoperative outcomes in gynecologic cancer surgery. Methods: The American College of Surgeons National Surgical Quality Improvement Program database was queried to identify all gynecologic oncology cases from 2013 to 2019. Clinical and surgical characteristics and 30 day postoperative complications were retrieved. The primary outcome was 30 day composite morbidity, based on the occurrence of one or more of the 18 adverse events. Secondary outcomes were 30 day mortality, length of stay in hospital, and composite surgical site infection, defined as superficial, deep, or organ space surgical site infection. The χ 2 test and logistic regression analyses were performed to compare the outcomes of patients with and without perioperative blood transfusion. Results: There were 62 531 surgical gynecologic oncology cases with an overall transfusion incidence of 9.4%. The transfusion incidence was significantly higher at 22.4% with laparotomy compared with 1.7% with minimally invasive surgery (p<0.0001). On multivariable analysis for laparotomy patients, blood transfusion was predictive of composite morbidity (adjusted odds ratio (OR) 1.65, 95% confidence interval (CI) 1.48 to 1.85) and length of stay in hospital ≥5 days (adjusted OR 9.02, 95% CI 8.21 to 9.92). In advanced ovarian cancer patients (n=3890), the incidence of perioperative blood transfusion was 40.8%. On multivariable analysis, perioperative blood transfusion was the most predictive factor for composite morbidity (adjusted OR 1.67, 95% CI 1.35 to 2.07) and length of stay in hospital ≥7 days (adjusted OR 9.75, 95% CI 7.79 to 12.21). Conclusion: Perioperative blood transfusion is associated with increased composite morbidity and prolonged length of stay in hospital. Preoperative patient optimization and institutional practices should be reviewed to improve the use of blood bank resources and adherence to restrictive blood transfusion protocols.